Synthesis and characterization of push-pull bithiophene and thieno[3,2-b]thiophene derivatives bearing an ethyne linker as sensitizers for dye-sensitized solar cells - Sara S. M. Fernandes (2017)
Five push-pull heterocyclic dyes 4-7, and 9 were synthesized and characterized in order to study the variations in the optical, electronic and photovoltaic properties induced by structural modifications, i.e. different spacer units and anchoring groups. The final push-pull conjugated dyes 6-7 and 9 are formed by a N,N-dimethylaniline donor moiety conjugated with bithiophene, ethynyl-bithiophene or ethynylthieno[3,2-b] thiophene spacers and cyanoacetic acid or rhodanine-3-acetic acid as anchoring group. The synthesis of the precursor aldehydes 4-5 was accomplished through a Sonogashira coupling, on the other hand, compound 8 was prepared by Suzuki coupling. Knoevenagel condensation of aldehydes 4, 5 and 8 with cyanoacetic acid or rhodamine-3-acetic acid afforded the final push-pull dyes 6, 7 and 9. Information on conformation, electronic structure and electron distribution was obtained by DFT and TDDFT calculations. This multidisciplinary study regarding the evaluation of the optical, redox and photovoltaic properties of the dyes reveals that compound 7, bearing an ethynyl-bithiophene spacer conjugated with a cyanoacetic acid anchoring group, has the highest conversion efficiency (3.51%) as dye sensitizer in nanocrystalline TiO2 solar cells. Co-adsorption studies were also performed for dyes 6-7 with N719 as co-adsorbent, and this enhanced dye efficiencies by 33e45%. The best cell performance was obtained by co-adsorbing N719 and dye 7 (75/25 vol%) with 4.66% efficiency.